Cobalt+Salt-Stressed Salvia officinalis: ROS Scavenging Capacity and Antioxidant Potency - Hülya Torun (International Journal of Secondary Metabolite, 2019)
Salvia officinalis L. (Lamiaceae) is one of the most widespread herbal species used in the food processing industry and for culinary and medicinal purposes. This work aimed to investigate changes in plant growth, water content, lipid peroxidation, H2O2, proline, and enzymes related to reactive oxygen species (ROS) detoxification including superoxide dismutase (SOD), peroxidase (POX), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR). Phenolic contents and antioxidant capacity values such as ferric ion reducing antioxidant power (FRAP), cupric ion reducing antioxidant capacity (CUPRAC) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging were studied under stress conditions of salt, cobalt and a combination of the two. No significant differences were found in relative water content and chlorophyll fluorescence under salt, cobalt and their combination. However, the osmotic potential and relative growth rate were enhanced with salt+cobalt compared to salt-treated plants. Salt and cobalt individually stimulated high antioxidant activity. High APX and GR activities were associated with the high proline accumulation in the sage plants under the combined effect of salt+cobalt. The combination decreased lipid peroxidation (TBARS), while H2O2 content was increased. This increase with the combined salt+cobalt effect may be associated with the decrease in CAT activity. Moreover, a strong correlation was found between TPC and TF content and antioxidant capacity measured via FRAP, CUPRAC and DPPH. The TPC, TF and antioxidant capacity values also increased under the salt+cobalt combination, suggesting an increase in antioxidant content in the sage leaves. Therefore, the combination of salt and cobalt improved the stress tolerance of S. officinalis.